Analisis Faktor Determinan Perilaku Konsumen Terhadap Keputusan Pembelian Produk Dalam Negeri Pada E-Commerce - Diar Muzna Tangke; Andriany, Dynne (International Forum of Researchers and Lecturers, 2024)
The Covid pandemic has caused changes in people's behavior in carrying out buying and selling transactions. Slowly, people become familiar with e-commerce applications so that the buying and selling process becomes efficient and effective. The purpose of this research is to determine the influence of consumer behavior in the form of cultural, social, psychological and marketing mix factors on purchasing decisions in e-commerce in the city of Ambon.The method used is a quantitative method with a sample size of 102 respondents, with the criteria being people who live in the city of Ambon. The sampling technique uses a purposive sampling method. Data analysis techniques use validity and reliability tests, classical tests, and multiple linear regression analysis. Consumer behavior in the form of X1 cultural factors, X2 social factors, X3 psychological factors and X4 marketing mix have a significant effect on purchasing decisions in e-commerce partially and simultaneously.